Combination of high-intensity ultrasound and hydrogen peroxide treatment suppresses thermal aggregation behaviour of myofibrillar protein in water. (15th January 2022) - Liu, Haotian; Wang, Zhi; Badar, Iftikhar Hussain; Liu, Qian; Chen, Qian; Kong, Baohua
Highlights: H2 O2 prevented heat-induced disulfide cross-linking, inhibiting myofibrillar proteins (MPs) thermal aggregation. High-intensity ultrasound (HIU) disrupted the filamentous myosin structure. HIU increased MP inner sulfhydryl accessibility, promoting blockage effect of H2 O2 . Combination HIU and H2 O2 could improve the thermal stability of MPs in water. Abstract: This study was aimed at evaluating the potential of high-intensity ultrasound (HIU, 450 W for 10 min) combined with hydrogen peroxide (H2 O2 ) having various concentrations (0, 50, 100, 200, 400, 800 μmol/g protein) to inhibit the thermal aggregation behavior of myofibrillar proteins (MPs) in water. The results indicated that the addition of H2 O2 interfered with the intermolecular sulfhydryl-disulfide interchange and inhibited the disulfide bond cross-linking. The H2 O2 -mediated conversion of cysteine to thiol derivatives appeared to be the primary mechanism of this effect. The HIU combined with H2 O2, especially at the H2 O2 concentration of 200 μmol/g, corresponded to a more significant inhibitory effect than that of only H2 O2, which attributed to the dissociation of the filamentous myosin structure that led to an enhanced accessibility of the buried sulfhydryl groups. In conclusion, these findings provide direct evidence for the role of HIU combined with H2 O2 in improving the thermal stability of MPs.